The Impact of Islamic Education Teacher Competence on Student Achievement in Elementary Schools - Meti Afrina; Aisyah Cantika; Nada Husniyah; Anggi Afrina Rambe (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
This study aims to determine how much impact the competence of Islamic Religious Education teachers has on student achievement in elementary schools. This study used a quantitative method with a correlation type, the data source was taken by using a questionnaire to twenty respondents, and the data were analyzed using Excel 2013. The results of the analysis showed that the teacher's competence obtained a calculated value of 0.41, while the r table was 0.44 at the level significant 5% and N = 20, the results of the analysis obtained that the calculated value < table value (0.41 < 0.44), it can be concluded that there is no relationship between the competency of Islamic Religious Education teachers and student achievement. The results of this study can be used as initial data for future researchers in examining different issues related to this problem and various other issues that are relevant to this context.